2015
DOI: 10.3174/ajnr.a4649
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Coiling versus Surgical Clipping for Poor-Grade Ruptured Intracranial Aneurysms: Postoperative Complications and Clinical Outcome in a Multicenter Poor-Grade Aneurysm Study

Abstract: BACKGROUND AND PURPOSE: Endovascular coiling is an alternative to surgical clipping for ruptured intracranial aneurysms. However, no large multicenter prospective study has compared coiling and clipping in patients with poor-grade ruptured aneurysms. We aimed to determine differences in postoperative complications and clinical outcome between the 2 treatments in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Although endovascular coiling is more commonly used than clipping for ruptured aneurysms, there were no significant differences in outcome between coiling and clipping [2,3]. Our research concerning the treatment of poor clinical condition after aSAH is similar to this viewpoint [4].…”
supporting
confidence: 65%
“…Although endovascular coiling is more commonly used than clipping for ruptured aneurysms, there were no significant differences in outcome between coiling and clipping [2,3]. Our research concerning the treatment of poor clinical condition after aSAH is similar to this viewpoint [4].…”
supporting
confidence: 65%
“…This study protocol was approved by the Chinese Ethics Committee of Registering Clinical Trials. Details of the registry have been published elsewhere 14 15. Poor-grade aneurysms were defined as a World Federation of Neurosurgical Societies (WFNS) grade of IV or V after subarachnoid hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
“…Mocco et al [31] reported that 35 (35.7%) of 98 patients received coiling, and there was also similar outcome between coiling and clipping for poor-grade aSAH. In our prospective and multicenter registry of 262 patients with poor-grade ruptured aneurysm, 133 (50.8%) patients received endovascular coiling within 21 days after poor-grade aSAH [53]. An unadjusted analysis showed that the rate of outcome (mRS 0-2 or mRS 0-3) at discharge at 6 and 12 months in the coiled patients was higher than that in the clipped patients probably because of selection bias.…”
Section: Endovascular Treatmentmentioning
confidence: 93%
“…Although endovascular treatment has been used as an available alternative to surgery for aSAH, surgical treatment is still an important treatment modality for poor-grade aSAH. In the contemporary multicenter cohorts of poor-grade aSAH, patients receiving clipping more often had a lower GCS score, a WFNS grade of V, a higher Fisher grade and modified Fisher grade, and a ruptured anterior circulation aneurysm than those receiving coiling [53]. Patients with WFNS grade V after emergency resuscitation, a better Fisher grade, brain herniation, the presence of ICH, or the absence of IVH more often underwent early surgical clipping [43].…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation